Effect of Iron-Erythrocyte Metabolism-Related Indexes on Posttraumatic Growth in Patients on Maintenance Hemodialysis (MHD) - Liang XR; Dong WH; Bi WD; Li JJ; Weng YQ; Zhang LJ; Guo ZY (International Journal of General Medicine, 2022)
Xin-Rui Liang,1,* Wen-Hao Dong,1,* Wen-Di Bi,2,* Jing-Jing Li,1 Yan-Qiu Weng,3 Ling-Juan Zhang,3 Zhi-Yong Guo1 1Blood Purification Center, Changhai Hospital of Naval Medical University, Shanghai, People’s Republic of China; 2Brigade One Team 2, Basic Medical College, Naval Medical University, Shanghai, People’s Republic of China; 3Department of Nursing, Changhai Hospital of Naval Medical University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ling-Juan Zhang; Zhi-Yong Guo, Tel +86-21-31162989 ; +86-21-31161406, Fax +86-21-31161411, Email lindazhang_cn@126.com; drguozhiyong@163.comPurpose: To investigate the effect of iron-erythrocyte metabolism-related indexes on posttraumatic growth in MHD patients and their caregivers.Patients and Methods: A total of 170 pairs of MHD patients and their caregivers in Shanghai Changhai Hospital were enrolled in this research, which used sociodemographic characteristics, the Posttraumatic Growth Inventory (PTGI), the Perceived Social Support Scale (PSSS), and the Medical Coping Modes Questionnaire (MCMQ). The test data of 141 patients were retrieved from the hospital database.Results: Single-factor analysis showed that the PTGI score of patients with a mean corpuscular erythrocyte volume ≥ 100 fL was 85.4 ± 19.8 and those with a mean corpuscular erythrocyte volume lower than 100 fL were 70.6 ± 24.7; the PTGI scores of patients with reticulocytes > 1.5% were 68.8 ± 25.8, and those with reticulocytes < 1.5% were 78.4 ± 21.1; the PTGI scores of the caregivers whose serum iron was > 10.6 μmol /L were 78.2 ± 21.6, and those with serum iron < 10.6 μmol /L were 67.9 ± 22.8. The difference in MCMQ scores between the caregivers with transferrin saturation> 50% and with transferrin saturation< 20% was 18.9 ± 8.4. For the correlation test of serum iron, reticulocyte and PTGI scores for patients, the Pearson correlation coefficients were 0.239 and − 0.193, respectively, and the correlation test between erythrocyte distribution width SD and the score of caregivers MCMQ scale, the Pearson correlation coefficient was 0.225; p for all was< 0.05, with significant differences. There was no significant difference in the scores of different scales for total iron binding capacity (TIBC) at different levels.Conclusion: The indexes related to iron erythrocyte metabolism in MHD patients are correlated with ruminant meditation of patients and their caregivers and promotion of posttraumatic growth. Good nutritional status, adequate hematopoietic material, and normal erythrocyte count and function are also important for them.Keywords: caregiver, patient, PTGI, PSSS, MCMQ